Doctor Who. The deadly assassin [videorecording (DVD)] - Baker, Tom, 1934-; Pratt, Peter, 1923-1995; Holmes, Robert, 1926-1986 (Tom Baker years, 1974-1981, 2009)
"Gallifrey. Planet of the Time lords. The Doctor has finally come home, but not by choice. Summoned by a vision from the Matrix, he is drawn into a web of political intrigue and assassination. Nothing is quite what it seems, and in the shadows lurks his oldest and deadliest enemy"--Container.